Canadian medical schools' preclerkship paediatric clinical skills curricula: How can we improve?. Issue 8 (6th October 2019) - Hudson, Alexandra; Mclaughlin, Robyn; Miller, Stephen; Holland, Joanna; Blake, Kim
Abstract: Background: Little is known about how Canadian medical schools teach paediatric clinical skills (history and physical exam) to preclerkship students, or its cost to the institutions. Methods: Clinical skills program directors from all 17 Canadian medical schools were contacted to complete a questionnaire focused on teaching methods, and barriers/strengths of their Preclerkship Paediatric Clinical Skills program. Results: Seventeen schools (100% response rate) participated. Seven schools (41%) do not introduce paediatric clinical skills until the second year of medicine. Half of the schools (53%) dedicate <10 total hours to preclerkship paediatric clinical skills. Fifty-nine per cent have ≤6 total hours of hands-on paediatric patient interaction (real or simulated). Medical students were least likely to be exposed to the infant age group (age 1 to 24 months). Twelve schools (71%) used simulated parent/child dyads. The most significant barriers identified by programs were limited time for sessions and patient availability. We describe one sample medical school's simulated parent/paediatric patient program where every student has hands-on learning with paediatric patients of all ages (program cost $938/student). Discussion: This study is the first to summarize Canadian preclerkship paediatric clinical skills programs, among which there is great variability and commonly experienced barriers. Many students are not being exposed to all age groups of paediatric patients before their clerkship years. Medical schools can use this information to strengthen this important and challenging aspect of the curriculum, while being mindful of its fiscal implications.